Perbandingan Penerapan Teknologi Ramah Lingkungan Di Universitas Pertamina Dengan University Of Wisconsin-River Falls - Meredita Susanty; Tiurmauli Rahel Ernita; Revyra Phoebe Fransiska; Ricky Suwandy; Farhan Akbar; Muhammad Fauzi Arda Saputra (JURNAL TEKNOLOGIA, 2020)
This research is aimed to maximize Universitas Pertamina’s (UP) eco-friendly efforts and change this relatively new university’s way of operation to be more eco-friendly and could rival the eco-friendliness of other instances by comparing the eco-friendly efforts of UP with University of Wisconsin–River Falls (UWRF) which is famous for their eco-friendly technology implementations. This Research is done by doing document analysis to acquire information regarding UWRF, as well as observation and interview to acquire information regarding UP. The comparison will visualize the good and bad sides as well as what can be improved of UP’s eco-friendly contributions. It can be concluded that UP still has many negative sides and needs to turn up their eco-friendly efforts if they want to compete with other instances Keywords: eco-friendly, UWRF, UP